Conceptual Challenges and dilemmas in the study of politics as a cultural system (Andamios, Revista de Investigación Social, 2012)
In the present we witness how a series of reconfiguration and uses everyday key concepts of the analytical body of contemporary political culture have generated a wide range of interpretations from political and social institutions with different nature, objectives and ideologies. In this scenario of dispute, the present work seeks, in the first place, complement a conceptual revision of the categories of citizenship and participation in order to overcome the standards and normalizations of political actor as a homogeneous subject. In addition, this paper presents challenges and weaknesses that face the categories of participation and citizenship as part of a conceptual framework in constant reconstruction and resignification.
Keywords: Political culture; political plural action; challenges and limits of the participation and citizenship